2023
DOI: 10.2337/cd22-0126
|View full text |Cite
|
Sign up to set email alerts
|

First Real-World Experience With Bigfoot Unity: A 6-Month Retrospective Analysis

Abstract: The Bigfoot Unity Diabetes Management System, a smart pen cap system cleared by the U.S. Food and Drug Administration in May 2021, incorporates continuous glucose monitoring data, real-time glycemic alerts, and clinician-directed dose recommendations. This study analyzed real-world clinical outcomes data for an initial cohort (n = 58, from 13 clinics) managing multiple daily injection insulin therapy using the pen cap system for 6 months. We examined glycemic control, including hypoglycemia events and interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Notably, there are no large, multicenter randomized control trials comparing connected pens or pen caps to vial and syringes or disposable insulin pens. Across all study types, these early studies show that connected pen systems are linked to higher time in range ( 26 , 28 , 30 , 31 ), reductions in A1c ( 29 , 31 ), reductions in severe hypoglycemia ( 20 , 26 ), reductions in missed insulin doses ( 26 , 28 , 29 , 30 ), and are a source of cost savings compared to standard insulin injections (nonconnected insulin pens or syringes) ( 19 , 20 ). Eckberg et al demonstrated that each missed basal insulin dose was associated with poorer glycemic management ( 27 ), illustrating that the dosage reminders from connected pen systems alone have the potential to improve glycemic outcomes.…”
Section: Scientific Literaturementioning
confidence: 98%
See 1 more Smart Citation
“…Notably, there are no large, multicenter randomized control trials comparing connected pens or pen caps to vial and syringes or disposable insulin pens. Across all study types, these early studies show that connected pen systems are linked to higher time in range ( 26 , 28 , 30 , 31 ), reductions in A1c ( 29 , 31 ), reductions in severe hypoglycemia ( 20 , 26 ), reductions in missed insulin doses ( 26 , 28 , 29 , 30 ), and are a source of cost savings compared to standard insulin injections (nonconnected insulin pens or syringes) ( 19 , 20 ). Eckberg et al demonstrated that each missed basal insulin dose was associated with poorer glycemic management ( 27 ), illustrating that the dosage reminders from connected pen systems alone have the potential to improve glycemic outcomes.…”
Section: Scientific Literaturementioning
confidence: 98%
“…Since then, eight clinical studies have been published ( Table 2 ). Of the eight studies included in Table 2 , three are based on Novo Nordisk’s NovoPen 6 ( 6 ), two investigate Medtronic’s InPen ( 20 , 28 ), two use the Insulclock pen ( 29 , 30 ), and one investigates Bigfoot’s Bigfoot Unity Diabetes Management System ( 31 ).…”
Section: Scientific Literaturementioning
confidence: 99%
“…(I) Waveform glucose monitoring technology-© WaveForm Technologies Inc. Wilsonville, OR, United States, all rights reserved; reference ( 144 ). (J) Smart insulin pen for personalized diabetes management-Copyright © 2023 American Diabetes Association, reference ( 145 ). (K) Tempo ™ personalized diabetes management platform consisting of a pen, Smart Button, App, and a smartphone-© Lilly Corporate Ctr., Indiana, United States, all rights reserved; reference ( 146 ).…”
Section: Wearable/implantable Wearable Biosensors In Continuous Gluco...mentioning
confidence: 99%
“…The Waveform cascade device is a 15-day CGM with a rechargeable transmitter approved in Europe in 2019, and communicates with a mobile app via Bluetooth with high accuracy ( Figure 5II, I ) ( 144 ). The Bigfoot Unity diabetes management system integrates a smart pen cap with the Freestyle Libre 3 to transmit insulin dosing information between the pen and mobile app ( Figure 5II, J ) ( 145 ). There are two versions of the pen cap, one for long-acting and the other for rapid-acting insulins.…”
Section: Wearable/implantable Wearable Biosensors In Continuous Gluco...mentioning
confidence: 99%